Giving more enhances your happiness: Evidence from Indonesia - Radikal Yuda Utama; Herman Palani; Ahmad Zufar Rabbani (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2021)
Previous studies revealed that consuming activities and spending money to meet needs can improve individuals’ happiness. Our study showed that spending money, not for personal needs also has a big impact on individuals’ well-being. We used 26,464 observations of 4th and 5th waves of the Indonesian Family Life Survey (IFLS) to predict the expenditures for non-personal needs (known as prosocial expenditure) on one's subjective well-being. The estimation result of the probit model showed that pro-social expenditure had a positive correlation with subjective well-being. On average, those who spend more on charity are happier than people who spend less. We also found that prosocial expenditure among Muslim and non-Muslim observations had different effects on happiness and life satisfaction.